Selectivity of sources: a case study of the "highlight" programme on NTA Ibadan (2000)
This study investigated the selectivity of sources of a current affairs programme on NTA Ibadan. Data were collected using the six content categories which included agriculture, economics, education, health, and general. The analysis of the highlight programme indicates that panelists are selected from various sources private practitioners (50%), university (32.8%), public (6.9%), research institutes (5.2%) and others (5.2%). However, the study shows that NTA Ibadan Highlight programme uses male panelists from private sources who are visible personalities, close associates and often comment on issues tangential to their disciplines.